Abdominal Aortic Aneurysm: Roles of Inflammatory Cells - Yuan, Zhen; Lu, Yi; Wei, Jia; Wu, Jiaqi; Yang, Jin; Cai, Zhejun (Frontiers in Immunology, 2021)
Abdominal aortic aneurysms (AAAs) are local dilations of infrarenal segment of aortas. Molecular mechanisms underlying the pathogenesis of AAA remain not fully clear. However, inflammation has been considered as a central player in the development of AAA. In the past few decades, studies demonstrated a host of inflammatory cells, including T cells, macrophages, dendritic cells, neutrophils, B cells, and mast cells, etc. infiltrating into aortic walls, which implicated their crucial roles. In addition to direct cell contacts and cytokine or protease secretions, special structures like inflammasomes and neutrophil extracellular traps have been investigated to explore their functions in aneurysm formation. The above-mentioned inflammatory cells and associated structures may initiate and promote AAA expansion. Understanding their impacts and interaction networks formation is meaningful to develop new strategies of screening and pharmacological interventions for AAA. In this review, we aim to discuss the roles and mechanisms of these inflammatory cells in AAA pathogenesis.